6 - The De-territorialization on Egypt’s Desert Cities: The Case of Sixth of October City - Khalil, Deena (Africa Development, 2023)
This article examines the application of ideas around the ‘de-territorialisation’ of cities in the global South to new desert cities surrounding Cairo, Egypt. It also responds to the call for ‘engaged theory-making’ by working with a local community development organisation on a case study of Sixth of October City (SOC), a new city in Cairo’s desert hinterland. Drawing on interview data, the article argues that a certain form of Western-inspired suburbanism has come to characterise Egyptian cities, stemming from the need to recirculate capital outside the existing cities. I propose three ways in which these desert suburbs are being de-territorialised. First, I argue that governance in the new cities is more focused on territorial transformation than on management of populations, and that this has resulted in what I describe as planned informality. Second, I show that housing in the new cities has become so financialised that even social (purportedly subsidised) housing has been integrated into circuits of capital. Finally, I demonstrate that there is a persistent form of inequality in basic services and infrastructure, and that the way the state governs the system of service provision has made it impossible for residents to develop alternative modes of access, resulting in an end to people’s ability to act as infrastructure.